Updating appetitive memory during reconsolidation window: critical role of cue-directed behavior and amygdala central nucleus - Olshavsky, Megan E.; Song, Bryan; Powell, Daniel J.; Jones, Carolyn E.; Monfils, Marie H.; Lee, Hongjoo J. (Frontiers in Behavioral Neuroscience, 2013)
When presented with a light cue followed by food, some rats simply approach the foodcup (Nonorienters), while others first orient to the light in addition to displaying the food-cup approach behavior (Orienters). Cue-directed orienting may reflect enhanced attentional and/or emotional processing of the cue, suggesting divergent natures of cue-information processing in Orienters and Nonorienters. The current studies investigate how differences in cue processing might manifest in appetitive memory retrieval and updating using a paradigm developed to persistently attenuate fear responses (Retrieval-extinction paradigm; Monfils et al., 2009). First, we examined whether the retrieval-extinction paradigm could attenuate appetitive responses in Orienters and Nonorienters. Next, we investigated if the appetitive memory could be updated using reversal learning (fear conditioning) during the reconsolidation window (as opposed to repeated unreinforced trials, i.e. extinction). Both extinction and new fear learning given within the reconsolidation window were effective at persistently updating the initial appetitive memory in the Orienters, but not the Nonorienters. Since conditioned orienting is mediated by the amygdala central nucleus (CeA), our final experiment examined the CeA’s role in the retrieval-extinction process. Bilateral CeA lesions interfered with the retrieval-extinction paradigm—did not prevent spontaneous recovery of food-cup approach. Together, our studies demonstrate the critical role of conditioned orienting behavior and the CeA in updating appetitive memory during the reconsolidation window.